THE STATE APPARATUS RESTRUCTURING IN VIETNAM - Anh, Dr Nguyen Ngoc (The journal of contemporary issues in business and government, 2021)
The state apparatus is the largest and important part of the political system in Vietnam, which functions on the principle of “Party‟s leadership, state‟s management and people‟s ownership”. While the Party exercises its leadership through selection, appointment, and management of personnel affairs as well as promulgation of resolutions and strategic documents on important issues of the country‟s socio-economic development, national defence, forein affairs, public security…, the state is responsible for carrying out the implementation of the Party‟s resolutions and decisions and held accountable before the Party on the results. The state apparatus in Vietnam follows a Soviet party-state style with heavy structure, numerous staffing, costly operation and low efficiency and effectiveness. The state sub-system includes the National Assembly, State President, central Government, People‟s Supreme Court and People‟s Supreme Procuracy and local authorities. Restructuring the state apparatus is key in the political system reform process in Vietnam as outlined by the Communist Party of Vietnam (CPV) Central Committee‟s resolution No. 18- NQ/TW dated 25 October 2017. There are strong actions in reviewing the organizational structure, reducing staff, merging agencies, administrative units, and positions with impressive results recently. However, this is a painful and uneasy process that used to fail in the past. Challenges are enormous, the inertia and resistance are strong. Therefore, it requires strong political will from the highest level, clear agenda for actions and orchestrated efforts from all related agencies and people in the political system.